Keillahian Yesus Kristus - Nursenta Dahliana Purba (Jurnal Teologi dan Pelayanan Kerusso, 2016)
When Jesus was born, it has caused turmoil in this world, even today. Who is Jesus really? Everyone can imagine and even think of Jesus according to their tastes. Starting from negative things, to positive ones. From insulting to praising. And that will still happen until the end of this world. Even though in Christianity Jesus is central to the faith of believers, the central Bible and the center of salvation. Then who exactly is Jesus as shown in Hebrews 1: 1-4? A true human and true Go d is present among humans.